Inter Relationship between Team Conflict Management, Employee Satisfaction and Organizational Performance - Rana, Asif Mehmood; ., Kashif-ur-Rehman (Information Management and Business Review, 2015)
Team work in competitive environment has attained greater Importance for organizations to enhance their performance. This paper is described the team conflict management with its antecedence like trust, task interdependence and managerial coping skill, whereas dependent variables i.e. team conflict management styles, employees satisfaction and organizational performance has been chosen as outcomes. To evaluate the deduction of other studies have been made part of this paper. This paper is conceptual in nature henceforth, relations between independently and dependent variables have been described. Studies proved that there is a strong relation between team conflict management with employeeâ€™s satisfaction and organizational Performance. It is recommended that to Executives, Managers Trust and Task interdependence between the team members have positive impact on TCMS (Team conflict management styles). Present paper provides the solution to handle the conflicts within the team and with the team. Future research is directed for its empirical testing of TCMS modelâ€ should be replaced with sound implication.